Kekuatan Lentur Papan Komposit Hasil Kombinasi Perentase Ijuk dan Cangkang Telur Ayam - Muhammad Mahdi; Syamsul Hadi (Jurnal Energi dan Teknologi Manufaktur, 2019)
The production of chicken egg is increasing every year, causing a lot of eggshell waste and abundance of natural materials of palm fiber (ijuk), but not used properly. The purpose of the research is to get the weight percentage variation of composite palm fiber and chicken eggshell with resin as a matrix. The method of this research include: the making of composite specimen from polyester resin Yukalac 157 BQTN-EX with added palm fiber and eggshell as a filler with sizes according to ASTM-D 7264, testing the composite specimens and Mahogany wood, and to analysis data from the test results is processed using Two-Way Anova to determine the effect of the percentage of palm fiber and chicken eggshell weights on flexure strenght composite. The result of flexural test show that the lowest yield strenght is on compotition of 4% palm fiber and 1% eggshell worth 11,3 MPa, and the highest yield strenght is on compotition of 9% palm fiber and 4% eggshell worth 87,7 MPa.